Ethical Aspects in the Assent of Adolescents to Participate in Research [Aspectos Éticos en el Asentimiento de Los Adolescentes Para Participar en Investigaciones] - Cancino-Jimenez, J (Sociedad Chilena de Pediatria, 2023)
Objective: to describe the ethical aspects to be considered in the consent of adolescents to participate in research. Material and Method: A narrative review was conducted in the scientific databases PUBMED and BVS, between 2010-2021, the search was conducted in English, and MeSH and DeCS descriptors were used, obtaining a total sample of 12 articles selected for analysis. Results: Age was commonly used instead of directly assessing the ability to understand the issues and make an informed decision about participating in research. This ability is influenced by age, context, and develo-pment. Adolescent decision-making is substantially different in the presence of peers. A balance is needed between recognizing the emerging autonomy in adolescents, their differential developmental rhythms, and their not yet fully mature response to personal risk. Conclusions: It is necessary to ge-nerate responses and strategies that safeguard both safety and respect for adolescents, focusing on the characteristics of both the age group and the individual, unifying valid mechanisms for determining the capacity to consent, integrating criteria from the sciences regarding cognition, maturation and development, psychology and ethics. © 2023, Sociedad Chilena de Pediatria. All rights reserved.